2020
DOI: 10.1136/bmjopen-2020-037731
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with non-initiation of mental healthcare after detection of poor mental health at a scheduled health check: a cohort study

Abstract: IntroductionPoor mental health is an important public health concern, but mental health problems are often under-recognised. Providing feedback to general practitioners (GPs) on their patients’ mental health status may improve the identification of cases in need of mental healthcare.ObjectivesTo investigate the extent of initiation of mental healthcare after identification of poor mental health and to identify factors associated with non-initiation.DesignProspective cohort study with 1-year follow-up.SettingIn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
2
1
Order By: Relevance
“…These findings may reflect increased perceived mental health burden in these individuals. Contrary to earlier studies ( Cornwell et al, 2021 ; Geyti et al, 2020 ), we did not find sex differences in initiating MHSU in individuals with MSS of depression and/or anxiety. This may in part be due to the fact that the majority (80%) of participants reporting MSS of depression and/or anxiety were female.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings may reflect increased perceived mental health burden in these individuals. Contrary to earlier studies ( Cornwell et al, 2021 ; Geyti et al, 2020 ), we did not find sex differences in initiating MHSU in individuals with MSS of depression and/or anxiety. This may in part be due to the fact that the majority (80%) of participants reporting MSS of depression and/or anxiety were female.…”
Section: Discussioncontrasting
confidence: 99%
“…In the context of important health service disruptions, shifting from in-person to virtual mental health care, and increased demand and limited access to mental health treatment during the pandemic ( Asmundson et al, 2020 ; Canadian Institute for Health Information, 2022b ; Duden et al, 2022 ; Mental Health Research Canada, 2020 ), few population studies have focused on the factors associated with initiating MHSU. A Danish study conducted prior to the pandemic showed that primary care patients having screened positive for depression and initiating mental healthcare within the year were more likely females and to report more severe impairment in mental health, while education, occupation and income differences were not observed ( Geyti et al, 2020 ). A Veterans Health Administration study in the USA showed that individuals initiating psychotherapy or antidepressant treatment within 3 months of a positive screen for depression were more likely to be females, to report anxiety or post-traumatic stress disorder, to be married, and to be younger than 44 years as compared to older age groups ( Cornwell et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This insight makes it easier for GPs to provide patient-centered counseling and ask questions that provide a holistic picture of the participant ( 65 ). Geyti et al addressed another aspect in their study, noting that the identification of PSPs does not necessarily lead to the initiation of treatment, where they see a need for further research ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…The initial questionnaire screening by SF-12 revealed low mental health among 9% of attenders, corresponding to the background population. Of these, 38.5% had no other high-risk factors according to their health check (Geyti et al, 2020). The intended follow-up at the GP for mental health care was seen for only one out of four with poor mental health, especially no follow-up when being disadvantaged socioeconomically (Geyti et al, 2018(Geyti et al, , 2020.…”
Section: Danish Studiesmentioning
confidence: 99%
“…Of these, 38.5% had no other high-risk factors according to their health check (Geyti et al, 2020). The intended follow-up at the GP for mental health care was seen for only one out of four with poor mental health, especially no follow-up when being disadvantaged socioeconomically (Geyti et al, 2018(Geyti et al, , 2020. Despite the free offer of follow-up on mental problems, the offer was not accepted by a majority of those with low mental health, perhaps because acceptance needs personal intervention (Geyti et al, 2020).…”
Section: Danish Studiesmentioning
confidence: 99%